Analisis Kebutuhan Terapi Wicara Pemuda Disabilitas saat Bernegosiasi di Dunia Kerja - Sabrina Lazuardian Insyirah; Silmi Kapatan Inda Robby (Bandung Conference Series: Public Relations, 2026)
Abstract. Sustainable development demands equity and the participation of all groups, including persons with disabilities. Although Indonesia has enacted Law Number 8 of 2016 on Persons with Disabilities, the level of formal labor force participation among youth with disabilities remains far below its potential. This disparity is primarily driven by social and psychological communication barriers that extend beyond physical obstacles, often leading to symbolic marginalization in the workplace. This study aims to analyze communication support needs, particularly the strategic role of Speech Therapy (ST), in strengthening the negotiation skills of youth with disabilities in sustainable professional interactions. Employing a qualitative literature review method, the synthesized findings indicate that the most urgent needs lie in training pragmatic skills (such as Turn-taking and topic maintenance) and assertive communication. ST interventions function as a vital instrument in building strong Self-Advocacy, enabling individuals to demand reasonable accommodations. The conclusion emphasizes the urgency of developing an Integrative Communication Support Model that fosters collaboration among Speech-Language Pathologists (SLPs), Job Coaches, and Organizational Social Support frameworks to achieve genuine workforce participation. Abstrak. Pembangunan berkelanjutan menuntut kesetaraan dan partisipasi semua kelompok, termasuk penyandang disabilitas. Meskipun Indonesia telah mengesahkan Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas, tingkat partisipasi angkatan kerja formal pemuda disabilitas masih jauh di bawah potensinya. Disparitas ini terutama disebabkan oleh hambatan komunikasi sosial dan psikologis yang melampaui hambatan fisik, yang sering kali mengarah pada marginalisasi simbolik di tempat kerja. Penelitian ini bertujuan menganalisis kebutuhan dukungan komunikasi, khususnya peran strategis Terapi Wicara (TW), dalam memperkuat kemampuan negosiasi pemuda disabilitas dalam interaksi profesional berkelanjutan. Menggunakan metode studi pustaka kualitatif, hasil sintesis menunjukkan bahwa kebutuhan mendesak terletak pada pelatihan keterampilan pragmatik (seperti Turn-taking dan topic maintenance) dan komunikasi asertif. Intervensi TW berfungsi sebagai instrumen vital untuk membangun Self-Advocacy yang kuat, memungkinkan individu menuntut akomodasi yang layak. Simpulan menegaskan urgensi pengembangan Model Dukungan Komunikasi Integratif yang kolaboratif antara Terapis Wicara (SLP), Job Coach, dan kerangka Dukungan Sosial Organisasi untuk mencapai partisipasi kerja yang sejati.